Gambaran Kadar Kreatinin Darah pada Penderita Jantung Koroner Berdasarkan Jenis Kelamin Metode Jaffe Reaction di RSUD H.A Sulthan Daeng Radja Kab. Bulukumba Tahun 2022 - Lely Nurfadilah; Dzikra Arwie; Muriyati Muriyati (PharmaCine : Journal of Pharmacy, Medical and Health Science, 2024)
Background: Coronary0heart0disease is a condition in which the arteries experience narrowing due to the accumulation of fat on the artery walls. Creatinine is the end product of creatinine metabolism. High or low blood creatinine levels are used0as0an important0indicator to find out whether0a person0has impaired-kidney function, because blood creatinine examination can be used as an indicator of the development of coronary heart disease which can cause kidney failure in a person. The Jaffe Reaction is the reaction between creatinine and picric acid in alkaline conditions to form an orange yellow compound which is measured using a spectrophotometer. Aim: To determine the description of blood creatinine0levels in0patients with0coronary0heart0disease based on the gender of the jaffe reaction method at H. A Sulthan0Daeng Radja0Hospital, Kab.0Bulukumba. Method: This research is a quantitative research with a cross-sectional descriptive design. The sample of this study were coronary heart patients at H. A Sulthan Daeng Radja Hospital, Kab. Bulukumba in August 2022, with a total of 42 sufferers. Result: The results obtained from 42 samples of blood creatinine levels increased in coronary heart disease patients, 7 men (54%) and 6 women (46%) with a total increase of 13 people. While normal creatinine levels in coronary heart patients were 16 men (55%) and 13 women (45%) with a normal total of 29 people. Conclusion: Based on the sex characteristics of coronary heart patients, it is known that out of a total of 42, 22 people were male, and 20 were female. Meanwhile, based on the age characteristics of the research subjects, there were 10 young people aged 35-50, 19 people 51-65, 11 people aged 66-75, 76-85 2 people. Based on examination of blood creatinine levels of 42 patients with coronary heart disease, there were 13 people who had increased blood creatinine levels, where a higher increase occurred in men, 7 people had blood creatinine levels (> 0.7-1.3 mg/dl). Meanwhile, 6 women had increased blood creatinine levels (>0.6-1.1 mg/dl). Keywords:  Coronary heart disease, blood creatinine levels